(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article focuses on the specifics of the construction and communication of Polish language courses and associated activities as a part of the Ukrainian School / Courses of Foreign Languages. They consider the semantic content of a textbook compliance with the requirements of the programs mentioned courses and expectations of students. It is shown that the simplified formula and selective presentation of the material in this manual may not match the competencies of teacher training and the level of the listener.